Vaccination coverage of primary care providers against seasonal influenza, tetanus, pneumococcal pneumonia and herpes zoster: A cross-sectional study in Greece - Panagiota Kalatzi; Antonios K. Travlos; Nickos Geladas; Maria Iliadou; Chara Tzavara; Costas Chryssanthopoulos; Alexandros Mihopoulos; Styliani Tziaferi (AIMS Press, 2023)
Introduction: Primary care providers' (PCPs) compliance to self-immunization is important for their protection and the protection of their colleagues and patients and has been associated with the coverage of the general public. In this study, we aim to investigate the vaccination coverage of PCPs. Methods: A questionnaire-based cross-sectional survey was conducted among physicians, nurses and pharmacists employed in public or private primary care settings in Greece. Demographic and occupational characteristics as well as vaccination coverage data for influenza, tetanus, pneumococcal pneumonia and herpes zoster were collected. Statistical significance was set at 0.05. Results: In total, 748 (61.7% response rate) PCPs participated. Vaccination rates were 66.4% (496/747) for influenza (2019/2020 flu season), 62.9% (469/746) for tetanus (10-year Td or Tdap booster dose), 70% (14/20) for pneumococcal pneumonia (≥ 1 dose of PPSV23 or PCV13) and 12.3% (10/81) for herpes zoster. Multiple logistic regression revealed that nurses had significantly lower probability of being vaccinated against influenza [odds ratio (OR) = 0.25; 95% confidence interval (CI) = 0.14-0.45] and pharmacists had significantly lower probability of being vaccinated against both influenza (OR = 0.44; 95% CI = 0.31-0.62) and influenza & tetanus (OR = 0.52; 95% CI = 0.37-0.73) compared to physicians. Older age (>40 years) was an independent risk factor for not receiving a tetanus vaccine (40-49 vs. 19-39; OR = 0.42; 95% CI = 0.28-0.63, over 50 years old vs. 19-39; OR = 0.54; 95% CI = 0.36-0.79). Conclusions: The results revealed suboptimal vaccination rates among health providers who are in the frontline of adult immunization. Individualized and targeted measures to improve their vaccination coverage and indirectly the vaccination coverage of their patients, are therefore required.